Domínio territorial, turismo e as populações originárias na Ilha do Bananal no governo Juscelino Kubitschek – 1955-1960 - Azevedo, Veruska Cavalcante (2024)
The objective of the research is to analyze Operation Bananal that took place in 1960, during the government of President Juscelino Kubitschek (1956-1960), which aimed to colonize and develop Bananal Island. It also seeks to develop a study on the Operation and its influences on territorial occupation, as well as the process of wild tourism in the interior of Brazil during the JK Government. The research was carried out within the qualitative method based on documentary analysis of original primary sources from Operação Bananal produced by Fundação Brasil Central. The Operation intensified the occupation of the Island, which generated negative consequences for the natural environment and the quality of life of indigenous populations. One of the assumptions about the reasons that led JK to carry out Operation Bananal is that he needed to divert attention from the massive expenditure on the construction of Brasília. Another hypothesis was to return to office in the 1965 elections and carry out large undertakings to impress and produce positive public opinion. This process can be considered as an invasion of the territory belonging to the indigenous people that resulted in significant losses for the ethnic groups that have inhabited the region since time immemorial. Operation Bananal carried out by JK demonstrated that the State promoted the reoccupation of the territory considering only the perspectives linked to the production and reproduction of capital, without taking into account the existence of the populations that lived there.